1990
DOI: 10.1182/blood.v75.12.2459.2459
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for chronic graft-versus-host disease after HLA-identical sibling bone marrow transplantation

Abstract: Chronic graft-versus-host disease (GVHD) is an important complication of bone marrow transplantation. We analyzed risk factors for chronic GVHD in 2,534 recipients of HLA-identical sibling transplants surviving at least 90 days after transplantation. The actuarial probability of developing chronic GVHD within three years posttransplant was 46% +/- 3% (95% confidence interval). The most important risk factor for chronic GVHD was acute GVHD. The 3-year probabilities of chronic GVHD were 28% +/- 3%, 49% +/- 5%, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
3
4

Year Published

1993
1993
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(89 citation statements)
references
References 21 publications
6
76
3
4
Order By: Relevance
“…We here report increased risks of acute GVHD grades I-II as well as chronic GVHD using low-dose CsA as GVHD prophylaxis. The physiological phenomenon underlying the increased incidence of both acute and chronic GVHD using low CsA is most likely similar; however, it is important to note that acute GVHD, as reported in the present study, may not be a major risk factor for chronic GVHD in recipients of HLA-identical sibling transplants (24), although some previous studies have shown a correlation between acute and chronic GVHD (28,29). When using the low-dose CsA regimen, approximately 25% of all patients still did not develop any acute GVHD.…”
Section: Discussionsupporting
confidence: 51%
“…We here report increased risks of acute GVHD grades I-II as well as chronic GVHD using low-dose CsA as GVHD prophylaxis. The physiological phenomenon underlying the increased incidence of both acute and chronic GVHD using low CsA is most likely similar; however, it is important to note that acute GVHD, as reported in the present study, may not be a major risk factor for chronic GVHD in recipients of HLA-identical sibling transplants (24), although some previous studies have shown a correlation between acute and chronic GVHD (28,29). When using the low-dose CsA regimen, approximately 25% of all patients still did not develop any acute GVHD.…”
Section: Discussionsupporting
confidence: 51%
“…Acute GVHD was assessed in patients surviving more than 21 d following engraftment using published criteria (Glucksberg et al, 1974). Chronic GVHD was defined using clinical criteria in patients surviving more than 90 d following engraftment (Atkinson et al, 1990).…”
Section: Methodsmentioning
confidence: 99%
“…14 In humans, the clinical relevance of mH antigens has been much more difficult to establish. The most important feature is the statistical demonstration of reduced risk of relapse in the case of sex mismatch (female donor, male recipient) as has been shown in retrospective series of allogeneic transplantation for leukemia [15][16][17] and in addition, a higher risk of GVHD. These statistical data were recently confirmed by a study demonstrating the direct association between mH antigen mismatch, GVHD, and relapse.…”
Section: Discussionmentioning
confidence: 99%